Morquio A Syndrome‐Associated Mutations: A Review of Alterations in the GALNS Gene and a New Locus‐Specific Database. Issue 11 (17th September 2014) - Morrone, Amelia; Caciotti, Anna; Atwood, Robert; Davidson, Kathryn; Du, Chaoyi; Francis‐Lyon, Patricia; Harmatz, Paul; Mealiffe, Matthew; Mooney, Sean; Oron, Tal Ronnen; Ryles, April; Zawadzki, Karl A.; et al.
<x xml:space="preserve">Abstract</x> The mutations in GALNS causing Morquio A syndrome are both extremely heterogeneous and feature a high proportion of rare alleles; consequently, the discovery of previously unpublished GALNS alterations from patients with Morquio A is a relatively common occurrence. From previously published data, we find 277 unique GALNS alterations associated with Morquio A. This up‐to‐date summary of known GALNS alterations and accompanying locus‐specific database will be a resource for the Morquio A community. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>